PEMANTAUAN TUMBUH KEMBANG ANAK MELALUI GIZI DAN POLA ASUH ANAK - Istiqomah Risa Wahyuningsih; Rina Sri Widayati (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2017)
In childhood, the process of growth and development happens very quickly. If food does not contain enough nutrients needed, and this situation lasts longer, it will cause changes in metabolism in the brain. This will result in the inability of the brain to function normally. In more severe and chronic conditions, nutritional deficiencies lead to aging body growth. The outcome target of community service is in the form of services aimed at improving the knowledge and participation of the community in monitoring the nutrition and growth of their children periodically. Method of implementation is done by counseling and question and answer. The results of this activity are held in Pulosari, Karangasem, Sroyo village on February 22, 2015, with the total number of 33 participants and the enthusiasm of the participants to follow the activities to completion. The conclusion of community service is the increase of knowledge and awareness as well as community participation related to nutrition and growth of their children.